2021
DOI: 10.1186/s40359-021-00693-5
|View full text |Cite
|
Sign up to set email alerts
|

Application of the dual-factor model of mental health among Chinese new generation of migrant workers

Abstract: Background Traditional models of mental health focus on psychopathological symptoms. In contrast, the dual-factor model of mental health integrates positive mental health and psychopathology into a mental health continuum, which is an adaptation and complement to the traditional mental health research paradigm. The new generation of migrant workers is an important part of current Chinese society. Their identity has created a sense of loneliness, rootlessness, and alienation. This paper validate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…For instance, China is in a period of social transition where migrant workers, as critical contributors to urbanisation, suffer an identity crisis characterised by loneliness and isolation. Therefore, paying attention to the mental health of Chinese migrant workers and improving their subjective social status and job satisfaction holds valuable practical implications for safeguarding their health rights and interests and improving their competitiveness for survival and development (Zhang et al, 2021). In light of the data analysis herein, we make the following recommendations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, China is in a period of social transition where migrant workers, as critical contributors to urbanisation, suffer an identity crisis characterised by loneliness and isolation. Therefore, paying attention to the mental health of Chinese migrant workers and improving their subjective social status and job satisfaction holds valuable practical implications for safeguarding their health rights and interests and improving their competitiveness for survival and development (Zhang et al, 2021). In light of the data analysis herein, we make the following recommendations.…”
Section: Discussionmentioning
confidence: 99%
“…Several empirical studies have affirmed that low subjective social status is accompanied by psychological pressure and negative perception, such as identity anxiety, negative emotion and shame, which have negative impacts on mental health (X. Li & Lyu, 2022; Zhang et al, 2021; Zhao et al, 2021). A few scholars believe the influence of subjective social status on mental health coming from social comparison, and that the sense of relative deprivation arising from upward social comparison leads to unfavourable mental conditions (Y.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, these conditions were identified using validated HBSC measures of mental well-being [ 31 ]. More specifically, two variables were considered as indicators of the two dimensions of the Dual Factor Model: LS was used as a proxy of subjective well-being, while PHC was adopted as a measure of mental illness, similar to some previous literature [ 14 , 32 ].…”
Section: Methodsmentioning
confidence: 99%
“…Based on the finding that employee PRESOR importance positively moderates the link between CSR and work outcomes, we expect that CSR will gain more relevance for Chinese HR management in the future. This is because the younger, better educated generation of Chinese employees has higher job expectations in terms of extrinsic and intrinsic work values (Huang et al, 2017;To & Tam, 2016;Zhang et al, 2021a) and in consequence, might attach greater importance to ethics and CSR performance of their employers. In light of the growing labor shortage in the blue-collar domain 1 and the associated rise in Chinese workers' bargaining power, CSR may allow Chinese businesses to better meet the changing demands of their workers in the future.…”
Section: Practical Implicationsmentioning
confidence: 99%